2022
DOI: 10.1038/s41413-022-00195-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cdk5 increases osteoblast differentiation and bone mass and improves fracture healing

Abstract: Identification of regulators of osteoblastogenesis that can be pharmacologically targeted is a major goal in combating osteoporosis, a common disease of the elderly population. Here, unbiased kinome RNAi screening in primary murine osteoblasts identified cyclin-dependent kinase 5 (Cdk5) as a suppressor of osteoblast differentiation in both murine and human preosteoblastic cells. Cdk5 knockdown by siRNA, genetic deletion using the Cre-loxP system, or inhibition with the small molecule roscovitine enhanced osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…(40) A wide variety of in vitro screening approaches have been employed to identify potential regulators of bone cell differentiation. (41)(42)(43)(44)(45) For example, high-throughput siRNA (41,42) and compound screens have identified small molecules such as roscovitine, rapamycin, and FK506, which augment osteoblast differentiation in vitro. (43) These approaches allow us to reduce animal experimentation by testing potential drugs at a cellular level.…”
Section: In Vitro Models For Skeletal Researchmentioning
confidence: 99%
“…(40) A wide variety of in vitro screening approaches have been employed to identify potential regulators of bone cell differentiation. (41)(42)(43)(44)(45) For example, high-throughput siRNA (41,42) and compound screens have identified small molecules such as roscovitine, rapamycin, and FK506, which augment osteoblast differentiation in vitro. (43) These approaches allow us to reduce animal experimentation by testing potential drugs at a cellular level.…”
Section: In Vitro Models For Skeletal Researchmentioning
confidence: 99%
“…It is anticipated that these advancements will facilitate the clinical translation of these inhibitors in the future. Inhibition of CDK5 has been shown to mediate the cell death of tumor-initiating cells (TICs), 148 promote the differentiation of ductal progenitors into β-cell, 149 promote the differentiation of osteoblasts and fracture healing, 150 reduce the proliferation of cancer cells and promote apoptosis, 73 and others. Despite the potential benefits of CDK5-selective inhibitors, progress in their development has been hindered at the primary stage.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, the pharmacological advantages of these drugs often come with unwanted consequences including gastrointestinal distress, osteonecrosis of the jaw, and hypocalcemia, thus restricting their prolonged usage . Besides, an increasing number of studies have demonstrated that antiresorptive medications do not stimulate bone regeneration and have little effect on patients with severe bone loss . Therefore, researchers are becoming increasingly interested in the development of natural bioactive substances that directly stimulate bone formation with fewer adverse effects as active constituents for the prevention of OP.…”
Section: Introductionmentioning
confidence: 99%
“…6 Besides, an increasing number of studies have demonstrated that antiresorptive medications do not stimulate bone regeneration and have little effect on patients with severe bone loss. 7 Therefore, researchers are becoming increasingly interested in the development of natural bioactive substances that directly stimulate bone formation with fewer adverse effects as active constituents for the prevention of OP.…”
Section: ■ Introductionmentioning
confidence: 99%